2014
DOI: 10.1109/tmag.2014.2327169
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Energy Harvesting by Amorphous Strips

Abstract: Magnetostrictive materials can play an important role in the realization of energy harvesters, a topic of growing scientific and industrial interest, because of their high-specific energy. Important applications are reported in the literature regarding Fe-Ga and rare-earth based harvester cores, but these materials are not suitable for exploiting low-energy vibrations. In this paper, we discuss the properties and behavior of a harvester based on a magnetostrictive amorphous core. It is made of a bundle of suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Zucca et al [43] presented an similar structure, as shown in figure 12, where the magnetostrictive beam was excited by a longitudinal tip force. A maximum power of 18 W m was achieved under a 300Hz, 1MPa amplitude sinusoidal axial stress [43]. In the single layer magnetostrictive beam designs, the bending deformation induces compression in half of the beam while causing tension in the other half.…”
Section: Bending Typementioning
confidence: 97%
“…Zucca et al [43] presented an similar structure, as shown in figure 12, where the magnetostrictive beam was excited by a longitudinal tip force. A maximum power of 18 W m was achieved under a 300Hz, 1MPa amplitude sinusoidal axial stress [43]. In the single layer magnetostrictive beam designs, the bending deformation induces compression in half of the beam while causing tension in the other half.…”
Section: Bending Typementioning
confidence: 97%
“…This outcome is not a foregone conclusion. As evidenced in [6,15], in the case of similar transducers, the current and power produced by the transducers have a maximum for a specific optimum magnetic bias. The mechanical vibration induces magneto-mechanical cycles, in terms of strain of the sample versus the applied magnetic field or versus the magnetic flux density.…”
Section: Cmentioning
confidence: 94%
“…The latter is a quantity related in a complex manner to the electrical and mechanical quantities. A detailed analysis in the case of the performance for magnetostrictive harvesters can be found in [6][7]. Here it is worth to mention how, in order to obtain repeatable measurements, one must check the following quantities: a) type of the active material (magnetic properties and electrical conductivity), b) temperature, c) vibration frequency, d) mechanical bias or preload, e) mechanical coupling between the coil and the active material, f) excitation stress amplitude, g) impedance of the coupled circuit, in addition to the coil resistance, h) state of magnetization of the magnets providing the magnetic bias.…”
Section: Quantitiesmentioning
confidence: 99%